2003
DOI: 10.1046/j.1365-294x.2003.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonconcordant evolutionary history of maternal and paternal lineages in Adriatic sturgeon

Abstract: Although analyses of intraspecific variability are an important prerequisite for species identification assays, only a few studies have focused on population genetics and historical biogeography of sturgeon species. Here we present the first study on genetic variability of the last remaining Adriatic sturgeon, Acipenser naccarii, derived from mitochondrial and nuclear DNA. Our mitochondrial DNA analyses arranged individuals into three distinguished mitochondrial DNA haplogroups (Po1, Po2 and Buna). Two haplogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 44 publications
(33 reference statements)
4
48
0
3
Order By: Relevance
“…introgression of the Woodhouse toad's mtDNA, Bufo woodhousii, into the Arizona toad, B. microscaphus, which has a nested range within B. woodhousii; Malmos et al 2001) or differences in population sizes (e.g. the Russian sturgeon, Acipenser gueldenstaedtii, introgressing mtDNA into the critically endangered Adriatic sturgeon, A. naccarii; Ludwig et al 2003). In many cases, authors could neither confirm nor rule out demographic explanations for observed discordance, where mtDNA introgression occurred because of variation in range sizes or preceding a population bottleneck and range expansion; however, most offered more specific explanations, such as adaptive introgression or sex-biased asymmetries.…”
Section: Box 3 Mitochondrial Structure In the Absence Of Geographic mentioning
confidence: 99%
“…introgression of the Woodhouse toad's mtDNA, Bufo woodhousii, into the Arizona toad, B. microscaphus, which has a nested range within B. woodhousii; Malmos et al 2001) or differences in population sizes (e.g. the Russian sturgeon, Acipenser gueldenstaedtii, introgressing mtDNA into the critically endangered Adriatic sturgeon, A. naccarii; Ludwig et al 2003). In many cases, authors could neither confirm nor rule out demographic explanations for observed discordance, where mtDNA introgression occurred because of variation in range sizes or preceding a population bottleneck and range expansion; however, most offered more specific explanations, such as adaptive introgression or sex-biased asymmetries.…”
Section: Box 3 Mitochondrial Structure In the Absence Of Geographic mentioning
confidence: 99%
“…Therefore, we suspect that there has been an introgression of mtDNA from an Asian Cobitis by hybridization. There are many examples of introgression of mtDNA in vertebrates (Dowling & De Marais, 1993;Duvernell & Aspinwall, 1995;Rhymer & Simberloff, 1996;Avise et al, 1997;Dowling & Secor, 1997;Ludwig et al, 2003, Freyhof et al, 2005. Freyhof et al (2005) demonstrated that introgression of mtDNA is not even restricted to closely related species or genera in one group of cypriniform fishes.…”
Section: Myxocyprinus Asiaticusmentioning
confidence: 99%
“…However, natural sturgeon hybrids are often rare (Ludwig et al 2002). Most times, backcrosses with native specimens resulted in a ''genetic cleaning'' of nuclear genotypes, so that evidence for ancestral hybridisation is often only detectable in mitochondrial DNA (Ludwig et al 2003;Birstein et al 2005).…”
Section: Introductionmentioning
confidence: 99%